2007
DOI: 10.1002/pen.20902
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoclays on the nucleation, crystallization, and melting mechanisms of isotactic polypropylene

Abstract: The influence of organomodified nanoclay (montmorillonite) on the crystallization and melting mechanisms of isotactic polypropylene (iPP) was studied. Films of both neat polymer and clay nanocomposites were prepared after molecular weight optimization through melt extrusion. Products exhibited the tactoidlike morphology since no compatibilizers were used. The effect of introduction of nanoclay within the polymer was studied through isothermal crystallization and linear heating. The results indicated that low n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…However, !-phase is occasionally observed during crystallization from melt. It can be obtained mainly by introducing specific nucleating agents in the melt using processing equipment such as extruders [13][14][15] incorporating an appropriate filler in micron and nanometer scale in the melt using internal mixers and extruders [16,17], inducing temperature gradients [18] and by shear forces in controlled flow fields [19][20][21]. A toughness improvement is associated to !-PP, being attributed to the development of a more perfect crystalline structure, with higher continuity of the amorphous phase and more connecting bridges between individual crystallites than a material containing solely "-crystallites [22]; and to the occurrence of a !-" transformation during loading which is accompanied with volume contraction in respect to the related crystallographic densities [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, !-phase is occasionally observed during crystallization from melt. It can be obtained mainly by introducing specific nucleating agents in the melt using processing equipment such as extruders [13][14][15] incorporating an appropriate filler in micron and nanometer scale in the melt using internal mixers and extruders [16,17], inducing temperature gradients [18] and by shear forces in controlled flow fields [19][20][21]. A toughness improvement is associated to !-PP, being attributed to the development of a more perfect crystalline structure, with higher continuity of the amorphous phase and more connecting bridges between individual crystallites than a material containing solely "-crystallites [22]; and to the occurrence of a !-" transformation during loading which is accompanied with volume contraction in respect to the related crystallographic densities [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the monoclinic form (a) presents a higher modulus, and the trigonal one (b) leads to a higher impact strength. Medellin-Rodriguez et al 23 detected the formation of b-crystalline structures in PP/clay nanocomposites and observed that the a form was the predominant structure, but the low clay concentration induced the formation of bcrystalline structures.…”
Section: Resultsmentioning
confidence: 99%
“…Flexural modulus tests were determined in an Instron Norwood, MA 4466 universal testing machine according to ASTM D 790. The Izod impact strength was determined at 23 C according to ASTM D 256 in a Resil Impactor Ceast Pianezza, Italy pendulum-type impact tester. The fracture surfaces of the Izod impact tested specimens were studied with scanning electron microscopy (SEM) in a JEOL JSM 6060 microscope operating at 10 kV.…”
Section: Characterizationmentioning
confidence: 99%
“…Avrami time constants were obtained by curve fitting on DSC experimental data for neat iPP crystallized at different temperatures 24 and iPP samples filled with 2 and 6 wt% of clay. 26 The modified Avrami model is examined to predict experimental crystallinity values of Misra et al's work. 17 Results in Figure 5 indicate that the proposed equation is capable of predicting crystallization behavior of PP clay composites up to 90% relative crystallinity.…”
Section: : ð4þmentioning
confidence: 99%